Learning Objects in Assisting Novice Programmers - Suriana, Ismail (2006)
It is always a challenge to teach first year computer programming subject. At MIIT-UNIKL, final exam result 2005 shows that introductory programming subject (Fundamentals of Programming) has the lowest average marks. It also contributes to the highest number of failure among other subjects. This study aims to develop learning objects prototype as an aided tools to help novice computer student in understanding programming concept better. Two learning objects prototype were developed. Semester one students were selected and divided into tested and control groups. The tested group evaluated the learning objects and involved in questionnaire session. Both groups involved in quiz session. The findings show that tested group has a higher passing rate as compared to the control group. Thus, it is believed that the learning objects can used as aided tools towards better performance of novice programmers.